How Managers Make Sense of Human Resource Management’s Role in Building Trust: Enacting Espoused Human Resource Management in Indian Gas and Petrol Public Sector Organisations - Kapoor, SJ; Ho, M; Anderson, D (ER Publishing Ltd, Auckland, 2022)
The desire to mobilise effective strategic human resource management in India’s new public management domain has seen the role of organisational trust receive greater scholarly and practical scrutiny. This study explores managers’ perception of HRM’s role in building organisational trust in five public sector organisations in India using exploratory multiple case studies. In implementing HRM, the findings suggest that managers are cognisant of specific human resource practices that can be socially adapted to enhance their effectiveness. Implications from the study’s emergent process model of human resource management and trust highlight the cross-level influences that affect India’s public sector organisations’ outcomes.
Keywords: India; Organisational trust; Public sector organisations; Strategic human resource management; Human resource management; Multiple case studies